Effect of inoculants and NPN additives on dry matter recovery and cattle performance: a summary of 22 trials - Bolsen, K.K.; Laytimi, A.; Pope, Ronald V.; Riley, Jack G. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Results from 22 trials comparing dry matter (DM) recovery and cattle performance of inoculated or non-protein nitrogen (NPN)-treated silages to controls were summarized using paired t-test analysis. Inoculants consistently improved DM recoveries and gains per ton of crop ensiled in both com and forage sorghums. The use of NPN adversely affected nutrient preservation and gain per ton of crop ensiled, particularly for the wetter forage sorghums.
Keywords: Beef; Innoculants; Non-protein nitrogen (NPN); Performance